Archaeology and paleogeography of a Lake‐Wetland complex: Modeling the postglacial evolution of the Kawartha Lakes, Ontario. Issue 4 (8th January 2020) - Conolly, James
Abstract: This study uses a combination of isostatic rebound, hydrological flow, and sedimentation models to generate predictions about the postglacial evolution (from ca. 12.0 ka cal BP to the modern‐day) of the Kawartha Lakes region of central Ontario, Canada. Changes in shoreline and wetland configuration are mapped and quantified so as to inform understanding of the environmental history of the region and illuminate the manner of its evolution. This knowledge is discussed in the context of the human history of the region, particularly the relationship between ancestral Indigenous communities and their relationship to lakes and wetlands. Areas of significant shoreline transgression are identified and thus where inundated archaeological sites are likely to exist. The scale of loss of wetland areas as a result of 19th‐century dam construction is also estimated along with the impacts of settler dams on Michi Saagigg Nishaabeg First Nations traditional harvesting practices.